Supply chain management performance and ERP implementation - Mohamed Udin, Zulkifli; Shatat, Ahmad Saleh (UUM Press, 2012)
Business management has entered the era of networking competition.This has moved the competition from a local to that of global business environments and from company against company to that of a supply chain against supply chain.Enterprise Resource Planning (ERP) systems have become one of the main pre-requisites and a strong and integrated IT infrastructure for many companies enabling them to compete and to gain a competitive advantage in the local and global marketplace.ERP systems are considered as the backbone for e-business as well as for the whole supply chain, particularly for those companies that undertake online business transactions.Supply Chain Management Performance and ERP Implementation is unique in its breadth of coverage the impact of ERP systems functionality on Supply Chain Management (SCM) performance with respect to Top Management Support, Employee Involvement, and Cultural Fit.It is presented and explained in a clear, straightforward manner based on the empirical data through a research.